Sequences upstream of AAUAAA influence poly(A) site selection in a complex transcription unit - DeZazzo, J D; Imperiale, M J (Molecular and cellular biology, 1989)
The adenovirus major late transcription unit (MLTU) encodes five colinear mRNA families, L1 through L5, each distinguished by a unique poly(A) site. Site selection is regulated during the course of infection, predominating early at the L1 site and late at the L2 through L5 sites. Two general mechanisms can be invoked to explain predominant usage of the L1 site early in infection. MLTU site selection may proceed in a first-come, first-serve manner whereby the L1 site is used most frequently because it is closest to the promoter. Alternatively, specific sequences flanking the L1 site may control predominant L1 site usage in a position-independent manner. To distinguish between these mechanisms, we constructed deletions in the L1 flanking sequences and inserted the mutated sites into either simple transcription units or mini-MLTUs encoding two poly(A) sites. The pattern of site selection for each construct was then quantitated by S1 nuclease analysis after transfection into 293 cells. The results indicated that L1 sequences upstream of AAUAAA define a novel selector element that can cause predominant L1 site usage at either position of a tandem transcription unit. The element did not significantly affect the stability or nucleocytoplasmic transport of L1 transcripts and was not required for efficient 3'-end processing in simple transcription units. Predominant L1 site usage required physical linkage of the processing signals and was independent of the major late promoter.